Knowledge and students’ use of university repository: a theoretical review (2022)
Institutional repository (IR) is an online locus deployed to manage intellectual outputs emanating from universities. Nigerian universities have witnessed an increase acceptance and subsequent contributions and use of the system. However, as the stem of the development keep increasing, there is a reported case of low awareness of the presence, types and usefulness of the systems particularly among the university studfents. The need to address this ugly development necessitated this study, a theoretical approach was employed and theories such as Actor Network Theory (ANT) as well as the Theory Constructivism were the theoretical frameworks were employed to underpin the study. The need to upscale effort at creating awareness on the type, purpose and potential benefits inherent in the IR was recommended as means of enhancing firm contribution and use of the system among the university community.